Using Conventional Rubric and Coh-Metrix to Assess EFL Students’ Essays - Mahadini, Monica Kristin; Setyaningsih, Endang; Sarosa, Teguh (Universitas Negeri Makassar, 2021)
The conventional scoring rubric has been used as a tool to assess students’ writing for years and recently there is growing attention on the use of automated assessment tools. While studies highlighting the use of the tools per se are numerous, not much is available on the use of the combined tools. This study addresses the gap by examining 20 university EFL students’ essays using both assessment tools. The essays were examined based on a conventional rubric which contains five aspects and two categories covering eleven indices of an automated tool called Coh-Metrix. The results of the examination were interpreted and information generated from the tools are compared. The study reveals that the use of both conventional and automated tools laid a more comprehensive picture of the students’ essays. The results of the assessment are useful to inform students and teachers on areas that need attention in the writing instruction. Gain and loss on the use of the tools are explained.